2021
DOI: 10.1016/j.jpain.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Contact Sports Results in Maintained Performance During Experimental Pain

Abstract: During pain, motor performance tends to decline. However, athletes who engage in contact sports are able to maintain performance despite the inherent pain that accompanies participation. This may be the result of being challenged rather than threatened by pain; adaptive coping strategies; habituation to pain; or finding pain less bothersome. This study aimed to measure performance of a novel motor task both in pain and not in pain within experienced contact athletes (n = 40), novice contact athletes (n = 40), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…The finding that NFL career length is significantly and negatively associated with affective aggression suggests that longer duration of professional participation in football actually decreases the odds of affective aggression later in life. While care should be taken not to overstate the significance of this finding, it is consistent with research showing that athletes who engage in contact sports are better than others at controlling their emotions when subjected to pain (Manning and Fillingim, 2002;Thornton et al, 2020). One interpretation of the present study's finding on NFL career duration could be that professional football trains participants to reign in and productively direct aggressive impulses as governed by the rules of the game, even in emotionally charged, paininducing situations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The finding that NFL career length is significantly and negatively associated with affective aggression suggests that longer duration of professional participation in football actually decreases the odds of affective aggression later in life. While care should be taken not to overstate the significance of this finding, it is consistent with research showing that athletes who engage in contact sports are better than others at controlling their emotions when subjected to pain (Manning and Fillingim, 2002;Thornton et al, 2020). One interpretation of the present study's finding on NFL career duration could be that professional football trains participants to reign in and productively direct aggressive impulses as governed by the rules of the game, even in emotionally charged, paininducing situations.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, in two experimental studies, athletes were better able than nonathletes to control their pain responses. Thornton et al (2020) found that athletes in contact sports were better able than athletes in noncontact sports to maintain their performance on a motor task during painful stimulation, a finding the researchers attributed to contact athletes’ perception of pain as a challenge rather than a threat. Manning and Fillingim (2002) also found that athletes had higher pain tolerances than nonathletes, which the athletes themselves attributed to competitive coping strategies.…”
Section: Other Relevant Correlates Of Anger Attacksmentioning
confidence: 99%
“…Team sport [7,8,11] Combat sport [3,4,7,8] Non-athletes [3,4,7,8,11] Non-contact athletes [7,8,11] Higher pain tolerance in contact sport athletes…”
Section: Tolerancementioning
confidence: 99%
“…Motor performance tests [8,27] were performed simultaneously with the pain condition in two studies to assess the interfering effects of pain. In both cases, the task required participants to throw a tennis ball at numbered targets in a given order.…”
Section: Motor and Cognitive Performance In Presence Of Experimentally Induced Painmentioning
confidence: 99%
See 1 more Smart Citation